2001
DOI: 10.1111/j.1574-0862.2001.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Market power and the pricing of commodities imported from developing countries: the case of US vanilla bean imports

Abstract: A declining trend in the prices of vanilla beans reduce export earnings of developing country exporters. At the same time, currencies for these developing countries have depreciated. The‘new’ trade theories suggest that market structure plays an important role in relating exchange rate devaluations to price declines. This paper investigates the market structure and estimates the impact of exchange rate movements on prices for vanilla beans imported by the USA from five producers of vanilla beans in developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…They found meager improvement in farmers' projected income and concluded that the sources of the remaining distortions stem from the malfunctioning of the market and imperfect information among farmers and traders. Moreover, substitutes for natural vanilla are now more widely used, which means there is more competition among suppliers in international markets and oligopsony among buyers (Rakotoarisoa and Shapouri 2001).…”
Section: Export Cropsmentioning
confidence: 99%
“…They found meager improvement in farmers' projected income and concluded that the sources of the remaining distortions stem from the malfunctioning of the market and imperfect information among farmers and traders. Moreover, substitutes for natural vanilla are now more widely used, which means there is more competition among suppliers in international markets and oligopsony among buyers (Rakotoarisoa and Shapouri 2001).…”
Section: Export Cropsmentioning
confidence: 99%
“…6,7 It requires a specific soil and particular climate conditions, so vanilla beans are expensive (first-grade extraction of vanilla beans from Madagascar hit between $475 and $500 per kilogram in 2019), 8 and the price fluctuates according to political and climatic conditions. 2,9 The main chemical constituents of vanilla extracts (Figure 1) are vanillin (4-hydroxy-3-methoxybenzaldehyde) and vanillic acid (4hydroxy-3-methoxybenzoic acid) with an average concentration of 135−175 mg/100 mL and 7−8.5 mg/100 mL, respectively. 10 Vanillin (C 8 H 8 O 3 ), an aromatic phenolic aldehyde, is the main aroma and flavor compound in the Vanilla planifolia black bean extracts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Antimicrobial, antioxidant, antimutagenic, anticarcinogenic, anticlastogenic, and antisickling effects are some of the biological activities that have been reported. , World vanilla production was 7575 tons per year in 2018 . Its production is highly labor-intensive (it should be harvested by hand and the bloomed flowers only last 1 day, when it has to be carefully pollinated within 12 h of blooming). , It requires a specific soil and particular climate conditions, so vanilla beans are expensive (first-grade extraction of vanilla beans from Madagascar hit between $475 and $500 per kilogram in 2019), and the price fluctuates according to political and climatic conditions. , The main chemical constituents of vanilla extracts (Figure ) are vanillin (4-hydroxy-3-methoxybenzaldehyde) and vanillic acid (4-hydroxy-3-methoxybenzoic acid) with an average concentration of 135–175 mg/100 mL and 7–8.5 mg/100 mL, respectively …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that the growth of exports and that of national economy could be accelerated following the introduction of export promotion schemes (Balassa 1975, Fitzgerald andMonson 1987). However, some recent empirical studies (Nogués 1990, Reinhart 1995, Barrett 1999, Rakotoarisoa and Shapouri 2001 have cast doubt on the ability of individual small exporting countries to take advantage of economic policies such as exchange rate adjustment or export promotion schemes for generating higher export revenues in the face of imperfectly competitive markets.…”
Section: Introductionmentioning
confidence: 99%